Clinical application of personalized oral care in patients with oral and maxillofacial diseases (个性化口腔护理在口腔颌面疾病患者中的应用) - CAI Shuang (蔡爽); LIANG Yu (梁宇); SUO Shuai (索帅); ZHI Shengrui (只升睿); WANG Meng (王蒙); LIU Xuewei (刘学伟) (Journal of International Translational Medicine Limited, 2022)
Objective To evaluate the application of personalized oral care in patients with oral and maxillofacial diseases. Methods Totally 200 patients with oral and maxillofacial diseases were randomly divided into two groups. Patients in the control group(n=100) were given routine oral care during the treatment, and those in the observation group(n=100) were given personalized oral care based on routine management. The therapeutic effect, incidence of complications, patient satisfaction with nursing service and compliance rate of the two groups were evaluated and compared. Results The therapeutic effect in the observation group was higher than that in the control group (98. 00% vs. 89. 00%, P＜0. 05 ). The satisfaction rate, incidence of complications and compliance rate of the observation group were better than those of the control group (P＜0. 05). Conclusion Personalized oral care could effectively improve the treatment effect, satisfaction and compliance rate of patients, facilitate the development of diagnosis and treatment, and then help to reduce the incidence of complications, promote the rehabilitation of patients and improve the quality of life. (目的 探讨个性化口腔护理在口腔颌面疾病中的应用效果。方法 将2019年1月-2021年1月收治的200例口腔颌面疾病患者随机分为观察组和对照组, 各100例。对照组给予常规护理, 观察组在对照组基础上开展个性化护理措施。观察组两组治疗效果、护理满意度、并发症发生情况以及治疗依从性。结果 观察组治疗总有效率98. 00%(98/100), 高于对照组的89. 00%(89/100), 差异有统计学意义(P＜0. 05)。观察组护理满意度91. 00%(91/100), 高于对照组的74. 00%(74/100), 差异有统计学意义(P＜0. 05)。观察组并发症发生情况优于对照组, 差异有统计学意义(P＜0. 05)。观察组依从率92. 00%(92/100), 高于对照组的83. 00%(83/100), 差异有统计学意义(P＜0. 05)。结论 口腔颌面疾病诊疗过程中采用个性化口腔护理干预, 有助于提高患者治疗依从性, 促进口腔功能恢复, 值得临床推广应用。)